Pleuroparenchymal fibroelastosis (PPFE) associated with giant cell arteritis: A coincidence or a novel phenotype?. (2019) - Perruzza, M.; Fusha, E.; Cameli, P.; Capecchi, P.L.; Selvi, E.; Gentili, F.; Mazzei, M.A.; Aversa, S.; Spina, D.; Di Lucia, D.; Sestini, P.; Luzzi, L.; et al.
Abstract: Pleuroparenchymal fibroelastosis (PPFE) is a rare interstitial lung disease characterized by the fibrotic thickening of subpleural and parenchymal areas of the upper lobes. It may be both idiopathic or secondary to infections, interstitial lung diseases and/or drug exposure. Often PPFE patients report recurrent lower respiratory tract infections, suggesting that repeated inflammatory alterations induced by pulmonary infections may contribute to the development/progression of PPFE. Here, we report for the first time the case of a patient affected by Giant cell Arteritis with histologically proven PPFE. The lung involvement in GCA is rare and interstitial lung diseases are usually reported as an uncommon clinical manifestation of GCA. Our patient is probably the first case presenting PPFE associated with GCA and we wonder if this is a real associative disease or a coincidence perhaps, secondary to drug effects.